The Impact of Differentiated Instruction on Learners' Social Interaction in Primary Schools - Kamalia, Nasywaa; Suprapmanto, Joko (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
The purpose of this study was to examine the impact of differentiated instruction on learners' social interaction in primary schools. This research applied the literature review method and analysed the data with a simplified approach to simplify the problem-solving process. The results show that the implementation of the differentiated instruction approach has a positive impact on learners' social interaction. This approach fosters cooperation in groups, through discussion, learners also develop their communication skills. Differentiated instruction not only plays a role in improving academic achievement, but also in shaping learners' character in socialising and empathising. The implementation of differentiated instruction shows effectiveness in increasing learning participation, so teachers should consider this approach in planning and implementing teaching. The results also support the view that flexible, learner-centred learning can create a learning environment that is inclusive, adaptive and supports the development of social and cognitive skills. This research can also serve as a reference to encourage teacher training to effectively implement the differentiated instruction approach.